Faktor-Faktor Yang Berhubungan Dengan Tingkat Stres Kerja Perawat Di Ruang IGD RSPAL Dr Ramelan Surabaya - Nety Mawarda Hatmanti; Novi Puspitasari; Chilyatiz Zahroh; Priyo Mukti Pribadi Winoto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Â to determine the factors related to the level of work stress of nurses in the emergency room at RSPAL Dr Ramelan Surabaya .Methods: Â The research design used descriptive research methods. The population of this study were 45 nurses in the Emergency Room of RSPAL Dr Ramelan Surabaya, the sample size was 45 people using total sampling and analyzed using chi square correlation. The variables used are age, gender, years of service, workload and work stress of nurses. The instrument uses a questionnaire.Results The results of the study of nurses aged 26-35 years, almost half of them experienced moderate nurse work stress, almost half of male nurses experienced mild nurse work stress, nurses with 3-5 years of work experience more than half experienced nurse work stress on a regular basis. moderate, nurses with a moderate workload mostly experienced moderate work stress.Conclusion: Â Nurses are expected to be used as a means of providing education to nurses on how important it is to deal with nurse stress at work.